2010
DOI: 10.1007/s11606-010-1450-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Follow-Up of an Abnormal Pap Smear in Latina Women Referred for Colposcopy

Abstract: BACKGROUND: Lower rates of follow-up after an abnormal Pap smear in racial and ethnic minorities may contribute to the higher incidence and mortality rates of cervical cancer seen in these groups. OBJECTIVE: To identify patient-perceived barriers to follow-up after an abnormal Pap smear result among Latina women. DESIGN, PARTICIPANTS AND APPROACH: Qualitative, semi-structured, one-on-one interviews were conducted with patients from an academic hospitalaffiliated urban community health center. Three groups of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 31 publications
7
56
1
Order By: Relevance
“…Other studies also report that women experience system issues with regard to follow-up care including inconvenient scheduling times, long clinic waits, and variations in healthcare services/procedures from clinic to clinic. 27,29,31,33,46,54 We did not find that women's characteristics were associated with interpersonal-level barriers, but it is important to note that the types interpersonal barriers slightly differed by ethnicity. African American women most commonly reported communication barriers related to not understanding information given to them by medical personnel.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Other studies also report that women experience system issues with regard to follow-up care including inconvenient scheduling times, long clinic waits, and variations in healthcare services/procedures from clinic to clinic. 27,29,31,33,46,54 We did not find that women's characteristics were associated with interpersonal-level barriers, but it is important to note that the types interpersonal barriers slightly differed by ethnicity. African American women most commonly reported communication barriers related to not understanding information given to them by medical personnel.…”
Section: Discussionmentioning
confidence: 66%
“…13 Studies have also found delay-related psychosocial barriers, including fear of pain associated with follow-up exams or with fear of cancer. 16,[27][28][29] Interpersonal factors associated with delays include inadequate communication or dissatisfaction with providers on test results or procedures. 27,28,30 System factors associated with delays include inconvenient appointment hours and long clinic waits; 29,31 having to seek care at larger hospitals; 32 first diagnostic appointment with radiology rather than a surgical consultancy; 32 and variations in healthcare services/procedures from clinic to clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for adherence included abnormality identification, patient activation, provider-initiated actions, and motivation from family or friends. Unlike some qualitative studies, 13,15,21,31 ours purposefully identified only reasons women directly attributed to adherence, thereby highlighting factors most proximal along the pathway to care decisions.…”
Section: Discussionmentioning
confidence: 99%
“…At the individual level, obstacles to care identified have included low education level, 10 poor health literacy, 11 concerns about test efficacy, 12 and language and cultural beliefs related to cancer, distrust, and fear. [13][14][15] Compounded with these concerns, systems barriers such as difficulty accessing highquality diagnostic services, 16 variability in site of care, 17 poor access to primary care physicians or specialists, 18 and lack of insurance, 19,20 can impact adherence to cancer-related care. Health care reform provisions target financial barriers to access to cancer care but will unlikely attenuate the full range of obstacles to care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation